Controlled manipulation of single atoms and small molecules using the scanning tunnelling microscope. Issue 9 (6th September 2013) - Morgenstern, Karina; Lorente, Nicolas; Rieder, Karl‐Heinz
<x xml:space="preserve">Abstract</x> Modern surface science employs the scanning tunnelling microscope not only to detect single atoms or molecules and to spectroscopically characterize them, but also as nanoscale 'tweezers' for the manipulation of individual adsorbates including single molecule chemistry. These capabilities open up new aspects of science on the smallest scale currently accessible in surface science. The three main manipulation modes accessible by STM are lateral manipulation, electron‐induced manipulation, and vertical manipulation. In the cover image, lateral manipulation is used to create the Bandenburg gate from CO molecules on a vicinal Cu surface, electron‐induced manipulation is used to switch an azobenzene derivative adsorbed on a thin NaCl layer between its trans‐ and its cis‐state. Vertical manipulation is used to pick up a CO molecule from the surface. For further details see the Review Article by Karina Morgenstern et al. on pp. 1671–1751. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>